Sexual quality of life and body image of breast cancer patients: uncovering the meaning behind the symptoms - Brajković, Lovorka; Korać, Dora; Jelić, Katarina; Kopilaš, Vanja (Psicooncología, 2024)
Introduction: Breast cancer symptoms and the side effects of treatment can significantly affect different domains of women’s functioning. Objective: The aim of this study was to examine the quality of life in women with breast cancer. Method: Our sample consisted of 240 women aged 30-68 (M=52, SD=8.68). Approximately 50% had undergone a mastectomy, while 40% had breast reconstruction. A structured questionnaire consisted of social-demographical data, SQOL-F, EORTC QLQ-C30 & EORTC QLQ-BR23. Results: Results suggest that our BC patients had lower quality of life and more financial difficulties than in most other studies, implying some cultural or health system differences. Not having a mastectomy was associated with better sexual quality of life, global health, and physical functioning. In contrast, women who underwent mastectomy reported impaired body image and sexual functioning, with more prominent breast symptoms. Reconstruction was related to the lower quality of life and no improvement in body image. Conclusions: Sexual quality of life was mainly related to global health status, emotional functioning, treatment side effects and body image. Emotional functioning and side effects were significant predictors of sexual quality of life, while impaired sexual functioning was associated with distorted body image. These findings can serve as guidance for forming interventions aimed at enhancing the quality of life.
Keywords: Breast cancer; sexual quality of life; body image